Reproductive Disorders and Seroprevalence of Brucellosis in Yak - Aryal, Sitaram; Paudel, Krishna P. (Nepal Agriculture Research Journal, 2014)
A study on reproductive disorders among yaks in Mustang and Solukhumbu districts and seroprevalence of brucellosis among yaks in Mustang and Myagdi districts was conducted. Eleven farmers having 383 female and 72 male yaks in Mustang and 129 female and 27 male yaks in Solukhumbu districts were taken by purposive random sampling for the study on reproductive disorders. Likewise Sixty-seven serum samples were also collected from adult female yaks having history of abortion and retained placenta, and from male yaks used for breeding purpose from Mustang and Myagdi districts. An average of 12.63% of female yaks aborted, 7.26% had had retention of placenta and 6.6% repeat breeders in Mustang district. Similarly, 6.3% had abortion, 2.09% retained placenta and 6.5% repeat breeders in Solukhumbu district. However, all the 67 serum samples examined were found negative to the Brucella abortus antibody on ELISA test suggesting that the yak population was free from brucellosis in these areas. Thus abortion and retention of placenta in Yak in Mustang district may not be due to brucellosis. A detail study should be done to find the specific cause of abortion and repeat breeding to recommend preventive and control measures. Nepal Agric. Res. J. Vol. 8, 2007, pp. 130-132 DOI: http://dx.doi.org/10.3126/narj.v8i0.11608